Internalisasi Nilai-Nilai Pancasila Melalui Kegiatan Kepramukaan di SMPN 17 Medan - Tampubolon, Stevanie Febiola; Sirait, Rose Venerius; Harahap, Putra Pratama; Sinaga, Eko Pranata; Jamaludin, Jamaludin; Yunita, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Character education is the process of instilling character valuesincludes the components of knowledge, awareness, desire and actionTo implement these character values, onea very popular and purported informal character education platformaims to instill these character values and formA good character for students is Scouting. Research methodsused in this research is qualitative with descriptiveQualitative. Results of research at SMPN 17 Medan implementation of activitiesThese scouts are quite good, with them practicing their valuesPancasila has shown that there are scout activities at the schoolit has been implemented well